2006
DOI: 10.1590/s0044-59672006000400010
|View full text |Cite
|
Sign up to set email alerts
|

Suco de açaí (Euterpe oleracea Mart.): avaliação microbiológica, tratamento térmico e vida de prateleira

Abstract: RESUMOUm dos principais problemas enfrentados quando da elaboração do suco de açaí é a contaminação por microrganismos, oriundas de problemas técnicos e higiênico-sanitários durante o processamento. Objetivando a erradicação desta microbiota no suco de açaí foram testados os processos de pasteurização e fervura em diferentes temperaturas e tempos e avaliou-se a vida de prateleira. Os sucos foram armazenados sob congelamento a -18 ºC por 120 dias e avaliados mensalmente quanto às características microbiológicas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 3 publications
3
8
0
11
Order By: Relevance
“…Analyzing samples of in natura açaí beverage commercialized in three fairs in Manaus-AM, Sousa et al (2006) also found high contamination by total and fecal coliforms, moulds and yeasts, corroborating with the results of this work.…”
Section: Proteinsupporting
confidence: 87%
See 1 more Smart Citation
“…Analyzing samples of in natura açaí beverage commercialized in three fairs in Manaus-AM, Sousa et al (2006) also found high contamination by total and fecal coliforms, moulds and yeasts, corroborating with the results of this work.…”
Section: Proteinsupporting
confidence: 87%
“…CFU.mL -1 of moulds and yeasts, which presented themselves at first as uncountable, decreased to 1.4 × 10 2 (Table 2) in the pasteurized treatment T 5 . Sousa et al (2006) also suggested that açaí beverage be submitted to the pasteurization process at 90 °C for 10 minutes as a way to decrease the high contamination rate that the açaí pulp presents. However, according to the author, the boiling process, despite having shown greater efficiency than pasteurization is not recommended, even for a short time period (1 minute), for influencing negatively the sensorial characteristics of the beverage.…”
Section: Proteinmentioning
confidence: 99%
“…Table 1 shows the experimental design used for the study of the heat treatment based on preliminary tests according to Rodrigues and Iemma (2005).The results were analyzed statistically using the software Statistica 5.0 (Stat Soft, Tulsa, the blanched pulp, a slight increase in acidity (1.39 %) can be seen for the most extreme time and temperature conditions, and also for the soluble solids content, which reached a maximum of 9.06 °Brix for the process realized under these conditions (96 °C/30 seconds). Similar results were found by Sousa et al (2006) in the pasteurization of acaí pulps using temperature/ time combinations of 90 °C/10 minutes and 100 °C/1 minutes.…”
Section: Microbiological Analysissupporting
confidence: 86%
“…A pasteurização torna-se um importante aliado na conservação de polpas por eliminar microrganismos patogênicos e também inativar enzimas. SOUSA et al (2006) avaliaram sucos de açaí tratados termicamente e constataram resultados microbiológicos de acordo com a legislação. Todas as amostras apresentaram ausência de Salmonella sp.…”
Section: Análises Microbiológicasunclassified